2003
DOI: 10.1107/s0021889803001833
|View full text |Cite
|
Sign up to set email alerts
|

Small-angle X-ray scattering study of the growth kinetics of CuCl nanocrystals in NaCl

Abstract: The precipitation of CuCl nanocrystals in a NaCl matrix has been studied by time-resolved small-angle X-ray scattering. The experimental results suggest that the nucleation process is accelerated by lattice defects of the matrix remaining in the NaCl lattice after the dissolution of previous nanocrystals at high temperature. The evolution of structural parameters calculated from the scattering curves, such as volume fraction, mean radius and particle number density of the nanocrystals, is discussed in terms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
2
2
0
Order By: Relevance
“…The calculated H mix values of β-(Ag 1– x Na x )­GaO 2 and (Ag 1– x Na x )Cl were slightly negative, whereas that of β-(Na 1– x Cu x )­GaO 2 was at most ∼4 kJ mol –1 . It was experimentally reported that AgCl and NaCl both possess a rock salt-type structure and form proportional solid solutions at 250 °C, whereas CuCl and NaCl possess zincblende-type and rock-salt-type structures, respectively, and form almost no solid solution . These experimental results are consistent with our calculations.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The calculated H mix values of β-(Ag 1– x Na x )­GaO 2 and (Ag 1– x Na x )Cl were slightly negative, whereas that of β-(Na 1– x Cu x )­GaO 2 was at most ∼4 kJ mol –1 . It was experimentally reported that AgCl and NaCl both possess a rock salt-type structure and form proportional solid solutions at 250 °C, whereas CuCl and NaCl possess zincblende-type and rock-salt-type structures, respectively, and form almost no solid solution . These experimental results are consistent with our calculations.…”
Section: Resultssupporting
confidence: 92%
“…It was experimentally reported that AgCl and NaCl both possess a rock salt-type structure and form proportional solid solutions at 250 °C, 39 whereas CuCl and NaCl possess zincblende-type and rock-salt-type structures, respectively, and form almost no solid solution. 40 These experimental results are consistent with our calculations. Based on this, it is reasonable to assume that NaCl and AgCl form a solid solution in the process of reaction 9, while CuCl and NaCl are segregated throughout the process of reaction 10, and there is no entropic gain due to ion mixing between them.…”
Section: Chemistry Of Materialssupporting
confidence: 92%
“…A ®xed distribution function of this type can be locally minimized against scattering data to yield a particle size distribution. Such a solution, however, is not unique and any number of possible particle size distributions could describe a given scattering curve (unless the distribution is extremely narrow) (Bolze et al, 2002;Dingenouts & Ballauff, 1999;Haubold et al, 2003;Kranold et al, 2003;Mulato & Chambouleyron, 1996;Mulato et al, 1998;Nakamura et al, 2003;Rieker, Hanprasopwattana et al, 1999;Rieker, Misono & Ehrburger-Dolle, 1999;Martelli & Di Nunzio, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years studies involving in situ X-ray diffraction using synchrotron radiation have increased tremendously and have proved to be milestones in studies of time-resolved crystallization and structural changes in several materials (Zolliker et al, 1990;Danzig et al, 1995;Morris et al, 1996;Svensson et al, 1997;Liang et al, 2003;Natter et al, 2000;Beale & Sankar, 2003). Although some studies use in situ X-ray diffraction (Danzig et al, 1995;Gualtieri et al, 1996;Natter et al, 2000) or small-angle X-ray scattering techniques (Vleeshouwers, 1997;Kranold et al, 2003) to study the kinetics of growth, crystallization and particle nucleation, such studies are conducted using only one detection system. Certainly, interest in these studies is of fundamental importance for controlling the synthesis and determining particle size and distribution as desired.…”
Section: Introductionmentioning
confidence: 99%